Electric bus charging station site selection based on the combined DEMATEL and PROMETHEE-PT framework. (June 2022) - Sang, Xiuzhi; Yu, Xianyu; Chang, Ching-Ter; Liu, Xinwang
Highlights: A framework of DEMATEL and PROMETHEE-PT is used to solve the site selection problem. The fuzzy PROMETHEE and PT is combined to obtain the ranking of the EBCS sites. The long-term is influencing coordination with power grid planning, total investment cost. Abstract: Electric buses (EBs) are one of the most promising transportation modes to reduce air pollution and greenhouse gas emissions. With the promotion of EBs, the selection of EBs charging station (EBCS) site plays a key role in bus electrification. In order to deal with the information uncertainty and the complicated logical relationship between evaluation criteria, this paper establishes a combined framework of fuzzy decision-making trial and evaluation laboratory (DEMATEL), preference ranking organization method for enrichment evaluations (PROMETHEE) and prospect theory (PT) to evaluate EBCS sites. Firstly, the evaluation criteria system consisting of transportation, economy, technology, and environment for the EBCS site selection problem is established. Secondly, the fuzzy DEMATEL method is adopted to calculate the weights of EBCS evaluation criteria and analyze their causal relationships. Thirdly, the fuzzy PROMETHEE method with PT is combined to obtain the ranking of the alternative EBCS sites. Finally, based on the case study in Nanjing city, the proposed combined framework proves to be effectiveness and scalability. The numerical results show that the long-term influencing criteria (e.g., coordination with power grid planning, total investment cost), the net cause criteria and the criteria with strong mutual influence have great impact on EBCS site selection.